2006
DOI: 10.1542/peds.2005-3052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Open-Loop Feedback on Physical Activity and Television Viewing in Overweight and Obese Children: A Randomized, Controlled Trial

Abstract: Providing feedback of physical activity in combination with reinforcing physical activity with sedentary behavior is a simple method of modifying the home environment that may play an important role in treating and preventing child obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 41 publications
1
103
1
3
Order By: Relevance
“…Many of the interventions reviewed can provide children with the skills needed to decrease screen-media use. Parents and clinicians should incorporate the interventions or the strategies that are common to the effective interventions into their efforts to combat childhood *Refs 44,91,95,96,98,100,[102][103][104]46,91,92,97,98,[102][103][104], and 110. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the interventions reviewed can provide children with the skills needed to decrease screen-media use. Parents and clinicians should incorporate the interventions or the strategies that are common to the effective interventions into their efforts to combat childhood *Refs 44,91,95,96,98,100,[102][103][104]46,91,92,97,98,[102][103][104], and 110. …”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] , 28 , [29][30][31][32][33][34][35][36][37][38][39][40][41] Recently, research has included developing and testing interventions that attempt to reduce children's screen time. [42][43][44][45][46][47] Although meta-analysis has been used to study the relationship between media use and weight and physical activity, 11 to date no systematic review and metaanalysis of interventions to reduce children's screen time has been completed. In this article we present the results of a systematic review and meta-analysis conducted to identify and examine the effectiveness of interventions to change children's screen time.…”
mentioning
confidence: 99%
“…Indeed, earning access to television has been used to incentivize physical activity in obese youth. 204 There also is emerging research on homebased interactive media games to bolster the reinforcing value of physical activity in obese youth. 72 The assessment of specific parenting practices that encourage or discourage physical activity and screen time will be important for assessing such treatments.…”
Section: Structuring the Home Environment To Reduce Child Screen Timementioning
confidence: 99%
“…This approach was then shown to be effective at increasing the physical activity of sedentary children over a 6-week period in the natural environment; in this study, the children's access to television was made contingent on achievement of a target number of counts on a Biotrainer accelerometer (where 400 counts earned 60 min of television time; Roemmich et al, 2004). A further study showed that obese children exposed to this contingency over an 8-week period showed significantly greater increases in daily physical activity than did control children who wore activity monitors to gain feedback on activity level but without behavioural goals or reward contingences (Goldfield et al, 2006). Such findings indicate that rewards combined with activity goals are effective above and beyond the effects of simply being able to monitor one's physical activity.…”
Section: Introductionmentioning
confidence: 97%